Guanine‐Stabilized Formamidinium Lead Iodide Perovskites. (3rd February 2020) - Hong, Li; Milić, Jovana V.; Ahlawat, Paramvir; Mladenović, Marko; Kubicki, Dominik J.; Jahanabkhshi, Farzaneh; Ren, Dan; Gélvez‐Rueda, María C.; Ruiz‐Preciado, Marco A.; Ummadisingu, Amita; Liu, Yuhang; Tian, Chengbo; et al.
Abstract: Formamidinium (FA) lead iodide perovskite materials feature promising photovoltaic performances and superior thermal stabilities. However, conversion of the perovskite α‐FAPbI3 phase to the thermodynamically stable yet photovoltaically inactive δ‐FAPbI3 phase compromises the photovoltaic performance. A strategy is presented to address this challenge by using low‐dimensional hybrid perovskite materials comprising guaninium (G) organic spacer layers that act as stabilizers of the three‐dimensional α‐FAPbI3 phase. The underlying mode of interaction at the atomic level is unraveled by means of solid‐state nuclear magnetic resonance spectroscopy, X‐ray crystallography, transmission electron microscopy, molecular dynamics simulations, and DFT calculations. Low‐dimensional‐phase‐containing hybrid FAPbI3 perovskite solar cells are obtained with improved performance and enhanced long‐term stability. Abstract : Guanin‐Perowskite : Die Stabilisierung der α‐FAPbI3 ‐Phase (FA=Formamidinium) wird in Form von Guaninium(G)‐basierten niederdimensionalen G2 PbI4 ‐Perowskiten realisiert, die Heterostrukturen bilden, die zu verbesserten Leistungen und Stabilitäten der entsprechenden Solarzellen führen. Die Struktureigenschaften werden untersucht, um ihren Wirkmodus zu entschlüsseln und den Weg für die Anwendung dieses Ansatzes in der Perowskit‐Solarzellforschung zu ebnen.